A novel, simplified, externally validated staging system for truncal/extremity soft tissue sarcomas: An analysis of the US Sarcoma Collaborative database. Issue 7 (27th September 2018) - Johnson, Aileen C.; Ethun, Cecilia G.; Liu, Yuan; Poultsides, George; Howard, John H.; Bedi, Meena; Charlson, John; Tseng, Jennifer; Roggin, Kevin K.; Votanopoulos, Konstantinos; Cullinan, Darren; Fields, Ryan C.; et al.
Abstract : Background: The 8th edition AJCC staging system for truncal/extremity soft tissue sarcoma (STS) offers significant changes from the 7th. However the complexity of both limits their clinical utility. Methods: Patients with truncal/extremity STS undergoing resection from 2000 to 2016 at seven institutions of the US Sarcoma Collaborative were analyzed. The proposed staging system was externally validated using the National Cancer Database (NCDB). Results: Of 1318 patients, mean age was 59 years, and 54% were male. Median tumor size was 9 cm; 72% were high grade. Applying 8th edition staging, there was no differentiation between stages IA/IB ( P = 0.92), and clinically similar outcomes between stages II/IIIA. Receiver operating characteristic (ROC) analysis identified 7.5 cm as the ideal tumor size discriminating 5‐year OS for high‐grade tumors. Therefore, a simplified staging system defining all low‐grade tumors as stage I, high‐grade < 7.5 cm as stage II, high‐grade > 7.5 cm as stage III, and metastatic disease as stage IV improved stratification (all P < 0.05). The C‐statistic was noninferior to the 8th edition. External validation in the NCDB confirmed optimal stratification (all P < 0.01). Conclusions: Our proposed staging system maintains prognostic significance between stages within a simplified system. For high‐grade tumors, a cutoff of 7.5 cm, instead of 5 cm, maintains discrimination for survival and could be a more clinically applicable cutoff for future clinical trials.